Why Should We (Not) Research Our Own Practice: The Perspective of Practitioners in Education - Мilan S. Stančić; Lidija R. Radulović; Оlja S. Jovanović Milanović (University of Belgrade, Teacher Education Faculty, 2022)
Starting from the insight that practitioners' research is increasingly being recognized as a form of professional development that contributes to the development of educational practice, the aim of our research is to determine the reasons for an insufficient representation of practitioners' research and explore the possible solutions for overcoming this problem. The data were collected during an online conference dedicated to professional development which was attended by 157 teachers and professional associates. The data corpus for analysis consists of participants' posts on the Padlet platform, namely, 156 posts dealing with the shortcomings of practitioners' research in relation to other forms of professional development and 106 posts on how to support other colleagues to overcome the aforementioned shortcomings. The data were analyzed using the qualitative content analysis. In the participants' opinion, the reason for an insufficient representation of the research of practice is the low motivation for this type of professional development, and they also cite the obstacles present at the level of school, education system, and society. According to the participants, the ways to overcome these problems include raising awareness of the benefits of research practice, taking responsibility for developing their own practice, and developing themselves as researchers, as well as building a community of research practitioners. The findings are discussed from the perspective of the conceptions of practitioners' research, but also from the perspective of the contextual conditionality of this form of professional development. The findings served to formulate recommendations for improving the position of practitioners' research and practitioners as researchers in the Serbian education system.